Form of Application of the Principle of Recognizing Service Users (Pmpj) by Land Deed Making Officials in Their Duties and Authorities - Pramadanty, Fathia Laely; Suhariningsih; Herlindah (The Islamic Education and Multiculturalism Foundation, 2024)
Based on the provisions in Article 4 of Government Regulation Number 43 of 2015 and Article 2 of the Head of Financial Transaction Reports and Analysis Center (PPATK) Regulation Number 11 of 2017, Land Deed Officers, hereinafter referred to as PPATs, have a crucial role as reporting parties. They have an obligation to carry out Service User Recognition Procedures (PMPJ), including identification, verification, and monitoring of transactions to ensure conformity with the profile of the individuals involved. The results of this PMPJ must be reported to PPATK for the benefit of the state. In addition, PPATs must also comply with ethical responsibilities, such as maintaining the confidentiality of client deeds and transactions; violating these obligations can lead to sanctions or violations. However, in practice, PPATs face challenges due to the lack of clear reporting forms from the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in short ATR/BPN, creating a confusing legal vacuum. Therefore, research on the implementation of PMPJ principles by PPATs is important to find appropriate solutions and ensure compliance with applicable regulations. The purpose of this research is to analyze and formulate the role of PPAT as a reporting party in the application of the Principle of Recognizing Service Users (PMPJ) in accordance with Government Regulation Number 43 of 2015 concerning Reporting Parties in the Prevention and Eradication of Money Laundering Crimes, as well as identify and explore the practical application of the Principle of Recognizing Service Users (PMPJ). The research method used is normative juridical research, to evaluate legal certainty regarding assessment in the implementation of PMPJ reporting by PPAT. The conclusion obtained from this research is that PPAT has an obligation as a reporting party in the implementation of the principle of recognizing service users to prevent and eradicate Money Laundering Crime (TPPU) in accordance with Government Regulation Number 43 of 2015. In this context, PPATs are directly responsible for identifying, verifying and monitoring service user transactions related to the purchase and sale of property, as well as engaging in a series of preventive measures to ensure compliance with the regulation